5a-2=a+6

To remove the radical on the left side of the equation, square both sides of the equation.

5a-22=a+62

Multiply the exponents in ((5a-2)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(5a-2)12⋅2=a+62

Cancel the common factor of 2.

Cancel the common factor.

(5a-2)12⋅2=a+62

Rewrite the expression.

(5a-2)1=a+62

(5a-2)1=a+62

(5a-2)1=a+62

Simplify.

5a-2=a+62

Rewrite a+62 as a+6.

Use axn=axn to rewrite a+6 as (a+6)12.

5a-2=((a+6)12)2

Apply the power rule and multiply exponents, (am)n=amn.

5a-2=(a+6)12⋅2

Combine 12 and 2.

5a-2=(a+6)22

Cancel the common factor of 2.

Cancel the common factor.

5a-2=(a+6)22

Divide 1 by 1.

5a-2=(a+6)1

5a-2=(a+6)1

Simplify.

5a-2=a+6

5a-2=a+6

5a-2=a+6

Move all terms containing a to the left side of the equation.

Subtract a from both sides of the equation.

5a-2-a=6

Subtract a from 5a.

4a-2=6

4a-2=6

Move all terms not containing a to the right side of the equation.

Add 2 to both sides of the equation.

4a=6+2

Add 6 and 2.

4a=8

4a=8

Divide each term by 4 and simplify.

Divide each term in 4a=8 by 4.

4a4=84

Cancel the common factor of 4.

Cancel the common factor.

4a4=84

Divide a by 1.

a=84

a=84

Divide 8 by 4.

a=2

a=2

a=2

Solve for a square root of 5a-2 = square root of a+6